False-Positive Results of SARS-CoV-2 RT-PCR in Oropharyngeal Swabs From Vaccinators - Kong, Xiang-Qi; Wang, Yong-Jing; Fang, Zan-Xi; Yang, Tian-Ci; Tong, Man-Li (Frontiers in Medicine, 2022)
Real-time reverse transcription-polymerase chain reaction (RT-PCR) is the gold standard for diagnosing coronavirus disease 2019 (COVID-19). However, RT-PCR may yield false-positive results, leading to unnecessary countermeasures. Here, we report a “positive” nucleic acid test on a 10-pooled sample during the routine screening that caused many adverse societal effects, and financial and resource losses. However, they were subsequently determined to be a case of vaccine contamination. This case study increases awareness of false-positive RT-PCR results for SARS-CoV-2, especially when participants are vaccinators. Moreover, it could provide relevant suggestions to prevent the recurrence of such incidents.